Given:
Mass of man 1(m1): 90 Kg
Mass of man 2 (m2):90 Kg
Distance between the two men (r) = x m
F(gravitational force) = 8.64 x 10^-8 N
Now we know that
Newton's law of universal gravitation states that all particle attract every other particle in the universe with a force . This force is directly proportional to the product of their masses. Also this is inversely proportional to the square of the distance between their centers.
This is mathematically represented as
F= (G X m1 x m2) /r∧2
where F is the gravitational force acting between the charged particles measured in N
r is the distance between the two charges measured in m
G is the gravitational constant which has a value of 6.674×10^-11 Nm^2 kg^-2
m1 and m2 are the masses of the objects measured in Kg
Now substituting the given values in the above equation we get
8.64 x 10^-8 = (6.674 X 10∧-11 x 90 x 90)/(r∧2)
Thus r=0.399 m
F= 3.3 X10∧-50 N